2015
DOI: 10.1080/10426914.2015.1019106
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Formation and Growth Mechanism of Nitride Layers During Plasma Nitriding Process of Plastic Injection Mold Steel

Abstract: Ion nitriding modifies composition of surface layer in steel used in plastic mold application and this consequently improves their lifecycle. In this study, pulsed plasma nitriding technique was used to produce a protecting hard layer on AISI P20 steel at three process temperatures of 450°C, 500°C and 550°C for durations of 2.5, 5, 7.5 and 10 hours at a constant gas mixture of 75% N 2 -25% H 2 . Surface morphology was studied by optical and scanning electron microscope (SEM) and the phases formed on the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Ion nitriding is widely used for hardening the surface of different machine parts [1,2]. It improves their corrosion [3][4][5][6][7], wear [8,9] and fatigue [10,11] resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Ion nitriding is widely used for hardening the surface of different machine parts [1,2]. It improves their corrosion [3][4][5][6][7], wear [8,9] and fatigue [10,11] resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As the forerunner of new materials, nano technology has been developing since 1980s as the focus of the research worldwide [1], and there into hard alloy with nano structure has been concentrated in the research for powder metallurgy [2][3][4]. Reports indicated that if the size of tungsten carbide(WC) crystalline particle was under 1μm, the hardness and tensile strength would increase synchronously, and the even remarkable increase of them could be observed for the nanostructured particle [5].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma nitriding process enhanced by an active screen is commonly used to improve corrosion behaviour and wear resistance of steels, titanium alloys, aluminum alloys, polymers and ceramics [1][2][3][4][5][6]. In this process, problems of conventional plasma nitriding like the edge effect are completely omitted since the plasma is produced on the screen not directly on the surface of sample [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%